Estevão Silva e Hélio Oiticica: brasilidade, a sensação revisitada - França, Cristina Pierre de (2002)
Investigation into Brazilian visual art, or better still into "Brasilidade". Its raison d'être is to show that there are characteristics of this issue ("Brasilidade") that have remained in the Brazilian art for longer than we imagine at first sight. "Brasilidade" can be defined as a private way of nationalism. It is thus connected with the feeling of belonging and the approach to a specific place or country, which is Brazil. This concept is the basis of the work, because it signs at the characterisation of "Brasilidade" found in the works of Hélio Oiticica (XX century) and Estevão Silva (XIX century) from two starting points: the sensation and the place. The place because the works of both artists send to this specific space that characterises Brazil. Estevão in the presentation of Brazilian fruits and Oiticica in the invention of environments that turn to that specific place. Secondly the workbody of both artists increase the sensation and the senses of the viewer. Estevão increases this by using virtuality; which amplifies taste in these pictures for by open fruits, ready to be delighted. Hélio uses this sensation too is amplified through the supra-sensorialidade when the viewers' perception is activated by their relationship with Hélio's work, they need to dance, to walk, to touch. More than mere coincidence, this work believes that this is one singular way for the Brazilian people to make their art.